To Analyze the Modifier Effect of NOS3 Gene in Hypertensive Patients of ADPKD (Academia Journal of Medicine, 2020)
Background: Nitric oxide is important for the functional integrity of the vascular endothelium and is produced in endothelial cells by the  enzyme endothelial nitric oxide synthase (eNOS). Hypertension has a strong genetic component, and the NOS3 gene, which encodes eNOS,  represents an interesting candidate for contribution to the phenotype. The most clinically relevant polymorphisms in the NOS3 gene are a  variable number tandem repeat (VNTR) in intron 4, and rs2070744 (T-786C) in the promoter region. Subjects and Methods: This study aims  to investigate the association between these three polymorphisms in the NOS3 gene and modifier effect on age, progression of disease and  hypertension in patients of ADPKD. Results: The present study carryout in the ADPKD patients admitted in NRI Medical College & Hospital. Univariate and multivariate logistic regression analyses were performed to assess the effect of genotypes and hypertension on the progress of  chronic kidney disease (CKD). A stratified analysis was also performed to assess the evidence of the modification of hypertension-CKD  relationship among VNTR genotypes. Conclusion: The results of this study indicated that the polymorphism in NOS3 may be a genetic  susceptibility factor for hypertension in the Indian population.
Keywords: VNTR genotypes; NOS3 gene; ADPKD; Hypertension